A sustainable molding process for new rubber products from tire recycling. Issue 1 (February 2019) - Quadrini, Fabrizio; Santo, Loredana; Musacchi, Ettore
A new technology has been developed to produce large-size rubber products by molding ground tire rubber (GTR) without using any binder or other substance. GTR is compression molded at high pressure and temperature to achieve an optimal particle adhesion. Large-size tiles (1 m 2 ) with thickness up to 50 mm have been molded without cracks or other damages. In this study, for the first time, energy consumption has been precisely estimated in different phases of the process cycle and discussed together with mechanical performances of molded products. Mechanical tests show that tiles have similar or higher performances than tiles produced by means of conventional processes (i.e. using polyurethane binders). Moreover, the new technology is able to save up to 50% of production costs related to electric energy and raw materials. Further developments are necessary to improve productivity by adding automation and reducing hand working.